„Exerzierplatz des Nationalsozialismus“ — der Reichsgau Wartheland in den Jahren 1939–1945 - Wichert, Wojciech (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of the article is the analysis of German policy in Reichsgau Wartheland, an area of western Poland annexed to Germany in the years 1939–1945. In scientific literature German rule in Warthegau with its capital in Poznań is often defined as ,,experimental training area of National Socialism”, where the regime could test its genocidal and racial practices, which were an emanation of the German occupation of Poland. The Nazi authorities wanted to accomplish its ideological goals in Wartheland in a variety of cruel ways, including the ethnic cleansing, annihilation of Polish intelligentsia, destruction of cultural institutions, forced resettlement and expulsion, segregation Germans from Poles combined with wide-ranging racial discrimination against the Polish population, mass incarceration in prisons and concentration camps, systematic roundups of prisoners, as well as genocide of Poles and Jews within the scope of radical Germanization policy and Holocaust. The aim of Arthur Greiser, the territorial leader of the Wartheland Gauleiter and at the same time one of the most powerful local Nazi administrators in Hitler‘s empire, was to change the demographic structure and colonisation of the area by the hundreds of thousands of ethnic Germans Volksdeutschen from the Baltic and other regions in order to make it a ,,blond province” and a racial laboratory for the breeding of the ,,German master race”. The largest forced labour program, the first and longest standing ghetto in Łódź, which the Nazis renamed later Litzmannstadt and the first experimental mass gassings of Jews in Nazi-occupied Europe carried out from autumn 1941 in gas vans in Chełmno extermination camp were all initiated in Warthegau, even before the implementation of the Final Solution. Furthermore, some of the first major deportations of the Jewish population took place here. Therefore in the genesis of the of the Nazi extermination policy of European Jewry Wartheland plays a pivotal role, as well as an important part of ruthless German occupation of Polish territories.
Keywords: Trzecia Rzesza; niemiecka okupacja Polski; Holokaust; Warthegau; Greiser, Arthur